Algoritma Quadtree Untuk Pendeteksian Tubrukan Pada Permainan Adventure Of Upik - Rahim, Robbi (STMIK TIME, 2014)
Many games in this life. The gameplay is outstanding and well known today simply highlight the benefits and as a medium for entertainment purposes only. And most children, teenagers and even adults make the game as the release of fatigue, as a busy entertainment center. Aside from being a means of entertainment, the Gamers usually also makes the game for commercial purposes. Usually this applies to the world of online gaming. adventure of upik aÂ game about little girl who got lost in the woods and away from home and parents, upik had to walk through the forest and had to fight the forces of evil mushrooms, snail and snakes that come attacked. This game uses a system of history is an adventure from start to finish beginning adventure complete the mission that has been designed. From the background of the above problems are obtained formulation of the problem is how to make the game called